Dynamic performance of Indonesian public companies: An analysis of financial decision behavior - Muchtar D.; Nor F.M.; Albra W.; Arifai M.; Ahmar A.S. (Cogent OA, 2024)
The purpose of this research is to investigate the effects of financial decision behavior on firm performance of Indonesian public companies using panel data. The dynamic generalized method of moment is utilized in this study. The results show that firm performance is dynamic in nature, which indicates that last year performance affects current performance significantly. Empirical result of financial decision behavior shows that investment, leverage, and dividend per share (DPS) have significant impact on firm performance. Specifically, investment has negative impact on firm performance. Meanwhile leverage has negative effects on return on assets (ROA), but positively affects Tobins Q. Moreover, DPS positively affects ROA and Tobins Q. This finding suggests that investment decision of Indonesian firms is overinvestment, indicated with higher investment affects firm performance negatively. Similarly with leverage, the finding reveals that Indonesian public companies borrowed external fund more than they required (overleverage). The positive effect of DPS on firm performance implies that dividends payout to shareholders create good signal to the market, in which managers uses dividend to deliver private information to the market. However, based on the coefficient of financial decision variables, the impact is more on the market performance and less on the accounting performance. 2018 The Author(s).